Body Composition and Physical Fitness Profiles of Elite Female Japanese Wrestlers Aged <12 Years until >20 Years - Hiroshi Arakawa; Daichi Yamashita; Takuma Arimitsu; Takashi Kawano; Takahiro Wada; Seshito Shimizu (MDPI AG, 2020)
Studies evaluating the physical fitness levels of elite wrestlers during junior high school are limited. This study aimed to examine the body composition and physical fitness profiles of elite Japanese female wrestlers aged <12 years until >20 years. There were 114 elite female wrestlers enrolled. Measurements were conducted in the following age categories: <12 years (U-12), <15 years (U-15), <17 years (U-17: cadet), <20 years (U-20: junior), and >20 years (senior). Body composition variables consisted of body mass index (BMI), percent body fat, fat free mass, and fat free mass index (FFMI). Fitness measurements included grip strength, back strength, sit-up, rope-climbing, and endurance running tests. The wrestlers in this study demonstrated comparable or greater FFMI values (e.g., FFMI: 17.9 ± 0.4 kg/m2 for light and 19.8 ± 0.9 kg/m2 for heavy weight categories in U-20), when compared with young female wrestlers in previous studies, whereas stature, body mass, and BMI of the wrestlers in our study were unremarkable. Regarding the fitness assessment, a remarkable increase in back strength was observed after late puberty. An outstanding enhancement of muscle strength after late puberty, which is unlikely to occur in ordinary women, would be an important requirement to become the world's top female wrestler.